2023
DOI: 10.1186/s13002-023-00584-6
|View full text |Cite
|
Sign up to set email alerts
|

Indigenous communities’ perceptions reveal threats and management options of wild edible plants in semiarid lands of northwestern Kenya

Abstract: Background Understanding how local communities perceive threats and management options of wild edible plants (WEPs) is essential in developing their conservation strategies and action plans. Due to their multiple use values, including nutrition, medicinal, construction, and cultural as well as biotic and abiotic pressures, WEPs are exposed to overexploitation, especially within arid and semiarid lands, and hence the need to manage and conserve them. We demonstrate how an understanding of indige… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 65 publications
0
1
0
Order By: Relevance
“…Biodiversity loss due to anthropogenic activity, ecological factors and natural causes are a matter of ongoing discussion worldwide. Threats for wild edible resources are not bereft out of it (Oluoch et al, 2023). In the present study, during group discussion some threats for the local WES have been identified.…”
Section: Threats Sustainable Harvesting and Conservation Practicementioning
confidence: 77%
“…Biodiversity loss due to anthropogenic activity, ecological factors and natural causes are a matter of ongoing discussion worldwide. Threats for wild edible resources are not bereft out of it (Oluoch et al, 2023). In the present study, during group discussion some threats for the local WES have been identified.…”
Section: Threats Sustainable Harvesting and Conservation Practicementioning
confidence: 77%